Mortality and PICU Hospitalization Among Pediatric Gunshot Wound Victims in Chicago. (11th February 2022) - Rhine, Maya A.; Hegermiller, Emma M.; Kane, Jason M.; Slidell, Mark B.; Mayampurath, Anoop; McQueen, Alisa A.; Mbadiwe, Nina; Pinto, Neethi P.
Abstract : IMPORTANCE: Firearm injury accounts for significant morbidity with high mortality among children admitted to the PICU. Understanding risk factors for PICU admission is an important step toward developing prevention and intervention strategies to minimize the burden of pediatric gunshot wound (GSW) injury. OBJECTIVES: The primary objective of this study was to characterize outcomes and the likelihood of PICU admission among children with GSWs. DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study of GSW patients 0–18 years old evaluated at the University of Chicago Comer Children's Hospital Pediatric Trauma Center from 2010 to 2017. MAIN OUTCOMES AND MEASURES: Demographic and injury severity measures were acquired from an institutional database. We describe mortality and hospitalization characteristics for the cohort. We used logistic regression models to test the association between PICU admission and patient characteristics. RESULTS: During the 8-year study period, 294 children experienced GSWs. We did not observe trends in overall mortality over time, but mortality for children with GSWs was higher than all-cause PICU mortality. Children 0–6 years old experienced longer hospitalizations compared with children 13–16 years old (5 vs 3 d; p = 0.04) and greater frequency of PICU admission (83.3% vs 52.9%; p = 0.001). Adjusting for severity of illness, children less than 7 years old were four-fold more likely to be admitted to the PICU than children 13–16 years old (aOR range, 3.9–4.6). CONCLUSIONS AND RELEVANCE: Despite declines in pediatric firearm mortality across the United States, mortality did not decrease over time in our cohort and was higher than all-cause PICU mortality. Younger children with GSWs experience longer hospitalizations and require PICU care more often than older children. Our findings suggest that the youngest victims of firearm-related injury may be particularly at-risk of the long-term sequelae of critical illness and injury.